PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM UNIT PENGOLAHAN PUPUK ORGANIK (UPPO) DI DESA SUNSEA - Dira A Pramita; Marselina TD Tea; Faustinus Kadha; Elisabeth Korbafo; Yohana Ivana Kedang; Ite MY Tnunay (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This community service program aims to empower farmers in Sunsea Village, Naibenu District, North Central Timor Regency, through the establishment of an Organic Fertilizer Processing Unit (UPPO) to process agricultural waste into solid and liquid organic fertilizer. Using a Participatory Rural Appraisal (PRA)-based training and mentoring method, the program was implemented from June to August 2024 through socialization, training in UPPO and organic fertilizer production, and monitoring and evaluation with the active participation of the community as facility providers and production actors. Results showed improved farmer skills in waste processing, cost efficiency of chemical fertilizers, independence in fertilizer production, and a reduction in organic waste that was previously burned or disposed of. Economic impacts include additional income through fertilizer marketing, while environmental benefits are realized from improved soil structure and reduced pollution. Key constraints include limited raw materials during the dry season, varied community skills, and limited marketing networks, which are addressed through storage systems, advanced training, and strengthening farmer groups. This program has the potential to be replicated in other agrarian villages to support sustainable agriculture.